SCAR Persistent Organic Pollutants Database - Scientific Committee on Antarctic Research (Zenodo, 2023)
A compilation of persistent organic pollutant data from Antarctica and the Southern Ocean, entered from journal and other publications. This database is accompanied by an interactive data exploration app at https://pops.apps.aq/ Data table schemas Sources data table - source_id: The unique identifier of this source - source_details: The bibliographic details for this source - source_notes: Relevant notes about this source – if it’s a published paper, this is probably the abstract - source_doi: The DOI of the source (paper or dataset), in the form "10.xxxx/yyyy" Main data table - source_id: The identifier of the source study from which this record was obtained (see corresponding entry in the sources data table) - original_record_id: The identifier of this data record in its original source, if it had one - location: The name of the location at which the data was collected - west: The westernmost longitude of the sampling region, in decimal degrees (negative values for western hemisphere longitudes) - east: The easternmost longitude of the sampling region, in decimal degrees (negative values for western hemisphere longitudes) - south: The southernmost latitude of the sampling region, in decimal degrees (negative values for southern hemisphere latitudes) - north: The northernmost latitude of the sampling region, in decimal degrees (negative values for southern hemisphere latitudes) - altitude_min: The minimum altitude of the sampling region, in metres - altitude_max: The maximum altitude of the sampling region, in metres - depth_min: The shallowest depth of the sampling, in metres - depth_max: The deepest depth of the sampling, in metres - observation_date_start: The start of the sampling period - observation_date_end: The end of the sampling period. If sampling was carried out over multiple seasons (e.g. during January of 2002 and January of 2003), this will be the first and last dates (in this example, from 1-Jan-2002 to 31-Jan-2003) - observervation_date_notes: Free-text field containing any notes about the ...